The national determinants of digital health: Health professionals’ electronic health literacy from a cross-sectional perspective in Ethiopia: An umbrella review - Mulugeta Desalegn Kasaye; Amare Gebrie Getahun; Asressie Molla Tessema; Nega Yimer; Mulugeta Hayelom Kalayou; Anas Ali Alhur (Digital Health, 2025)
Background Electronic health literacy is an emerging skill that needs to be focused on by the health system. Adopting and utilizing digital/electronic health tools helps healthcare providers with evidence-based decision-making during patient care. Therefore, pooling robust evidence could help determine the magnitude of health professionals’ level of electronic health literacy. Methods We used PubMed, Science Direct, EMBASE, African Journal Online, Google Scholar, and HINARI to search for systematic review studies. The study procedure was performed using the PRISMA flow diagram. We employed the revised version of the Assessment of Multiple Systematic Reviews (AMSTAR-2) checklist to score the quality of the included studies. The pooled effect size of the outcome variable was determined via a forest plot. Results Generally, three systematic review studies addressing 16 primary studies were included. Nearly 6435 study participants with an outcome of interest were included in this umbrella review. The overall pooled magnitude of good e-health literacy among health professionals was 55% (95% CI: 50, 60; I 2  = 94.4%). The average pooled effect-size of good eHealth literacy was positively associated with perceived usefulness, educational status, favorable attitudes, internet access, and perceived ease of use, 2.29 (95% CI: 1.82, 2.76), I 2  = 0.0, P  = 0.990. Conclusions A moderate level of eHealth literacy was discovered. It is mandatory to improve healthcare professionals’ internet access, as they are the first front-line information users in their duty of care. It is desirable to design programs and policies to strengthen national eHealth literacy by providing pertinent digital skill booster training regarding electronic health tools, enhancing the positive attitudes of health professionals toward easing and using digital tools to help patients access the most up-to-date information across the area of care. Furthermore, building mechanisms to gain and increase the knowledge of health professionals is a mandatory task for every sector of the health system.